INOVASI PELAYANAN ADMINISTRASI DAN KEPUASAN MASYARAKAT DESA DI ERA PANDEMI COVID-19 - Abdul Shomad; Neneng Fauziah (Politeknik STIA LAN Makassar, 2023)
The Corona Virus Disease (COVID-19) pandemic has changed many things, including public services. All levels of government are adapting to the new normal so that public services do not stop completely or are temporarily suspended due to the COVID-19 pandemic. Public services at the village government level have also changed. Lambangsari Village Government, Bekasi Regency, also innovated administrative services for the community. The COVID-19 pandemic has forced the village government to innovate so that public services can continue. This study aims to describe the innovation and satisfaction of the people of Lambangsari Village with public services in the village. This research uses a quantitative descriptive method with a Likert scale (Rensis Likert) as a measuring tool for the level of public satisfaction and a qualitative method to describe the administrative innovations carried out. Literature reviews, documentation, interviews, and questionnaires all served as data collection methods. The results of the study revealed that the government of Lambangsari Village carried out public service innovations in the form of mobile administration services and ball pick-up administration services. The level of community satisfaction with public services during the COVID-19 pandemic was good. Even so, the service innovations carried out did not have a significant impact on satisfaction. The community prefers conventional services by coming directly to the village office.